Platelet-to-lymphocyte ratio and neutrophil-to-lymphocyte ratio as predictors of refractory anaphylaxis - Nghi, Le Vinh; Phuc, Nguyen Hoang; Hai, Pham Dang (The World Allergy Organization journal, 2024)
Refractory anaphylaxis poses an ongoing, lethal hypersensitivity response that unpredictably involves multiple organs despite appropriate intramuscular (IM) adrenaline injections. Studies on the association of the platelet-to-lymphocyte ratio (PLR) and neutrophil-to-lymphocyte ratio (NLR) concerning anaphylactic severity have yet to be carried out. The study aimed to evaluate the association between blood PLR and NLR levels and refractory anaphylaxis. We carried out a retrospective cross-sectional study in which medical records of patients with anaphylaxis who sought urgent care at the Emergency Department (ED) of Tertiary Hospital in Hanoi, Vietnam, were evaluated. Based on the United Kingdom Resuscitation Council guidelines in 2021, patients were classified as refractory anaphylaxis if they needed more than two appropriate doses of intramuscular adrenaline for anaphylactic symptoms resolution. Clinical data and laboratory results were obtained in the medical records. Logistic regression analysis determined the association between contributing factors and refractory anaphylaxis. One-hundred eighteen adults (age 51.80 ± 18.25 years) were analyzed, including 38 refractory anaphylaxis patients (32.2%). Refractory anaphylaxis patients exhibited notably elevated platelet-to-lymphocyte ratio (PLR) (P = 0.006) and increased neutrophil-to-lymphocyte ratio (NLR) (P < 0.001) in comparison to non-refractory anaphylaxis patients. Receiver operating characteristic curve (ROC) analysis demonstrated an optimal PLR cutoff value of 129.5 (area under the ROC curve [AUC] 0.658, sensitivity 73.68%, specificity 61.25%, P = 0.004) and an optimal NLR cutoff value of 4 (AUC 0.736, sensitivity 65.79%, specificity 73.75%, P < 0.001) for refractory anaphylaxis. Multivariate logistic regression analysis revealed a PLR≥129.5 (OR = 4.83, 95% CI: 1.87–12.48) and an NLR≥4 (OR = 4.60, 95% CI: 1.86–11.41) were independently associated with refractory anaphylaxis. Elevated PLR and NLR serve as independent indicators significantly associated with refractory anaphylaxis.